Contactless probing of polycrystalline methane hydrate at pore scale suggests weaker tensile properties than thought - Dyhia Atig (Nature Portfolio, 2020)
The authors here report tensile properties of polycrystalline methane hydrate at the micron scale by applying a contactless, thermos-induced stress to a tenuous shell of hydrate grown in a thin glass capillary. The results suggest that the cohesive strength of methane hydrate in marine settings may be an order of magnitude less than currently thought.